Salmonellosis: An Overview of Epidemiology, Pathogenesis, and Innovative Approaches to Mitigate the Antimicrobial Resistant Infections - Bibek Lamichhane; Asmaa M. M. Mawad; Mohamed Saleh; William G. Kelley; Patrick J. Harrington; Cayenne W. Lovestad; Jessica Amezcua; Mohamed M. Sarhan; Mohamed E. El Zowalaty; Hazem Ramadan; Melissa Morgan; Yosra A. Helmy (Antibiotics, 2024)
Salmonella is a major foodborne pathogen and a leading cause of gastroenteritis in humans and animals. Salmonella is highly pathogenic and encompasses more than 2600 characterized serovars. The transmission of Salmonella to humans occurs through the farm-to-fork continuum and is commonly linked to the consumption of animal-derived food products. Among these sources, poultry and poultry products are primary contributors, followed by beef, pork, fish, and non-animal-derived food such as fruits and vegetables. While antibiotics constitute the primary treatment for salmonellosis, the emergence of antibiotic resistance and the rise of multidrug-resistant (MDR) Salmonella strains have highlighted the urgency of developing antibiotic alternatives. Effective infection management necessitates a comprehensive understanding of the pathogen’s epidemiology and transmission dynamics. Therefore, this comprehensive review focuses on the epidemiology, sources of infection, risk factors, transmission dynamics, and the host range of Salmonella serotypes. This review also investigates the disease characteristics observed in both humans and animals, antibiotic resistance, pathogenesis, and potential strategies for treatment and control of salmonellosis, emphasizing the most recent antibiotic-alternative approaches for infection control.